PENGARUH MODEL KOOPERATIF TIPE NUMBERED HEADS TOGETHER TERHADAP HASIL BELAJAR IPS DI SD - Faradila, Novia; Zuardi, Zuardi; Yunisrul, Yunisrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThe purpose of this research was to know the effect of the use of cooperative learning model type Numbered Heads Together (NHT) on the results of learning IPS five grade students SD Negeri Gugus IV Kecamatan Baso Kabupaten Agam. This research is a quantitative research with of Quasi Experimental Type Nonequivalent Control Group Design. The sampling technique using Cluster Random Sampling technique with the sample number 44 students consisting of 20 students of class V SD Negeri 11 Koto Gadang and 22 students of class V SD Negeri Sungai Sariak. Based on the research that has been done, obtained tcount > ttable that is 2,547079>1,68385  with α = 0,05 so it can be concluded H1 accepted that there is influence the use cooperative learning model type Numbered Heads Together on student learning outcomes in social studies learning at grade 5th in SDN 11 koto gadang. Keywords : Cooperative Learning, NHT, Learning Outcomes, IPS